Effects of Smartphone-Delivered Positive-Word Stimulation on Depressed Mood in People with Subthreshold Depression: Protocol for a Pilot Randomized Controlled Trial - Ejiri H (Dove Medical Press, 2021)
Hitomi Ejiri,1 Hiroyuki Uchida,2 Kenji Tsuchiya,1,3 Kazuhiko Fujiwara,4 Senichiro Kikuchi,1,3 Kazuki Hirao1,3 1School of Health Sciences, Faculty of Medicine, Gunma University, Maebashi, Japan; 2Department of Rehabilitation, Kurashiki Heisei Hospital, Kurashiki, Japan; 3Graduate School of Health Sciences, Gunma University, Maebashi, Japan; 4Department of Rehabilitation Sciences, Faculty of Rehabilitation Sciences, Nishikyusyu University, Kanzaki, JapanCorrespondence: Kazuki HiraoGraduate School of Health Sciences, Gunma University, 3-39-22 Showa, Maebashi, Gunma, 371-8514, JapanTel/Fax +81-27-220-8952Email kazuki.hirao@gunma-u.ac.jpBackground: Major depressive disorder (MDD) is an important public health problem. Thus, preventive interventions against subthreshold depression (StD), which is one of the key risk factors for the development of MDD, are important. The study developed a smartphone application (SPSRS) that improves depressive symptoms in people with StD by automatically presenting positive word stimuli during videos. The SPSRS application has the potential to improve depressive symptoms in people with StDs. However, whether it can immediately improve depressed moods in people with StD is unclear. The study presents a protocol for investigating the immediate effects of the SPSRS application intervention on depressed mood in people with StD.Methods: The study is designed as an open-label, parallel-group, and pilot randomized controlled trial (RCT). Thirty-two people who meet the criteria for StD (Beck Depression Inventory-II score of 10 points or more and fails to meet the diagnostic criteria for MDD) will be recruited and studied. It compares the immediate effects of the SPSRS application intervention (with positive word stimulus in a 10-minute video; n = 16) and YouTube application intervention (without positive word stimulus in 10-minute video; n = 16). The primary outcome is the change in the score for the Profile of Mood States 2nd Edition-Adult Short after 10 minutes of intervention. The secondary outcome is the change in the State–Trait Anxiety Inventory State after 10 min of intervention.Discussion: The pilot RCT is the first to evaluate the immediate effects of the SPSRS application intervention on depressed mood in people with StD. The results are expected to provide a preliminary outcome of the immediate effect of the SPSRS application on the depressed mood of people with StD and aid in planning a full-scale trial.Trial Registration: ClinicalTrials.gov; Identifier: NCT03864484.Keywords: depression, subthreshold depression, depressed mood, mobile application, smartphone